Methods of electrochemical energy storage control: classification and aspects of implementing - Sergiy Plaksin; Mykola Zhytnyk; Ruslana Levchenko; Svitlana Ostapovska (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
When an electrochemical energy storage is used as part of an energy system, the influence of external factors significantly changes its basic parameters: its available capacity decreases, while its internal resistance and self-discharge increase, which reduces the lifespan of the storage and disrupts the normal functioning of the energy system as a whole. Improving the performance of the energy storage is an urgent challenge, and one way to address it is to efficiently monitor the storage’s status. The purpose of this study was to increase the efficiency of using electrochemical energy storages by choosing a proper control method according to operating conditions of the storage. The conducted analytical overview of the existing methods of monitoring electrochemical energy storages allowed systematizing and classifying them by the controlled parameters. It is shown that if the storage operates in dynamic modes, such as buffer, starter or main energy source mode, when connecting high-power resistors, it is necessary to take into account such parameters as activation resistance and activation capacitance characterizing storage’s resistance capabilities and presenting valuable information for choosing the method of storage control. The paper demonstrates that in dynamic operation modes it is necessary to use impulse methods of storage control, which allow for efficient monitoring taking into account activation parameters. The authors offer practical recommendations on choosing a method of storage control depending on its operation mode. Pulse multistage potentiostatic and single-pulse galvanostatic control methods meet such requirements the most when the storage is operating in dynamic modes. The preference is given to the single-pulse galvanostatic method developed by the authors, it being relatively simple to implement and sufficiently informative for practical purposes, which facilitates the automation of the control process. Experimental results on controlling the electrochemical energy storage operating in dynamic modes obtained using the method developed by the authors confirm its efficiency.